تقنيات الشعر التعليمي في منظومة الشيخ محمد الطاهر التليلي ( في غريب القرآن ) - علال سليمة; شعلان خولة (University of Eloued جامعة الوادي, 2025)
الملخص: التعليم آلة من الآلات التي واجهت بها الجزائر الاستعمار في مشاريعه الرامية إلى مسخ شخصيتها، ومن هنا جاءت قيمة كبيرة للمعلمين الذي جابهوا الاستعمار بالتعليم، والشيخ الطاهر التليلي أحد هؤلاء، فقام البحث على فكرة النظر في تقنيات التعليم التي توسّل بها التليلي لتحقيق ما تقصده ورمى إليه، والغاية من هذا الكشف عن مدى وعي التليلي كممثل لمشايخ الجزائريين بالتعليم من حيث هو فن، وصناعة تقوم على أصول وعلى مقولات علمية منهجية. ولقد انتهى النظر التطبيقي في منظومة في غريب القرآن إلى أن تقنيات التعليم كلها ذات حضور واضح في وعي التليلي التعليمي، سواء ما اتصل منها بالمتعلم (=المتلقي) أو المعلَّم (=المادة التعليمية). وما كان هذا إلا بيانا وتبيينا لقيمة هذا العقل العلمي الذي أثبت قدرته على مجابهة التجهيل الاستدماري وقد كان. Summary: Education is one of the tools that Algeria used to confront colonialism in its projects aimed at distorting its character. Hence, the great value of the teachers who confronted colonialism with education, and Sheikh Taher Tlili is one of them. The research was based on the idea of examining the educational techniques that Tlili used to achieve what he intended and aimed for. The aim of this is to reveal the extent of Tlili’s awareness, as a representative of Algerian sheikhs, of education as an art and an industry based on principles and methodological scientific propositions. The applied study of the system "In the Strange Words of the Qur'an" concluded that all educational techniques have a clear presence in the educational consciousness of Tlili, whether they relate to the learner (=recipient) or the teacher (=educational material). This was nothing more than a demonstration and clarification of the value of this scientific mind, which has proven its ability to confront colonial ignorance, and it has.
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: التعليم المقاوم - الاستعمار الفرنسي في الجزائر - الشيخ الطاهر التليلي - تقنيات التعليم; Éducation à la résistance - Colonialisme français en Algérie - Cheikh Taher Tlili - Techniques pédagogiques